2017
DOI: 10.2135/cropsci2016.03.0177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variances and Relationship among Traits of an Early Maturing Maize Population under Drought‐stress and Low Nitrogen Environments

Abstract: Drought and low soil nitrogen (low N) are major causes of low grain yield of maize (Zea mays L.) in sub‐Saharan Africa (SSA). An early maturing maize population, TZE‐Y Pop DT STR, had undergone four cycles of selection for drought tolerance, followed by four selection cycles for resistance to Striga hermonthica (Del.) Benth., which is normally conducted under low N (about 30 kg N ha‐1). The objectives of this study were to estimate residual genetic variances, predict future gains from selection, and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 28 publications
(52 reference statements)
7
51
4
Order By: Relevance
“…A plausible reason for this was that the emphasis of the breeding program was more on improvement in drought tolerance rather than performance of cultivars under rainfed environments. The results of this study are inconsistent with the findings of Talabi et al (2017), who identified ASI, EASP, PASP, STGR, and EPP as the primary traits directly responsible for the variability in grain yield of early-maturing full-sib progenies under drought stress. In addition to marker-assisted selection and genomic selection, several other strategies outlined by Masuka et al (2017b) for increasing genetic gains in ESA breeding pipeline are being used in WCA under the Drought Tolerant Maize for Africa (DTMA)/Stress Tolerant Maize for Africa (STMA) Project for accelerating genetic gains.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A plausible reason for this was that the emphasis of the breeding program was more on improvement in drought tolerance rather than performance of cultivars under rainfed environments. The results of this study are inconsistent with the findings of Talabi et al (2017), who identified ASI, EASP, PASP, STGR, and EPP as the primary traits directly responsible for the variability in grain yield of early-maturing full-sib progenies under drought stress. In addition to marker-assisted selection and genomic selection, several other strategies outlined by Masuka et al (2017b) for increasing genetic gains in ESA breeding pipeline are being used in WCA under the Drought Tolerant Maize for Africa (DTMA)/Stress Tolerant Maize for Africa (STMA) Project for accelerating genetic gains.…”
Section: Discussioncontrasting
confidence: 99%
“…With the recent advances in molecular breeding techniques, marker-assisted selection and genomic selection schemes are presently being used to fast-track breeding processes and accelerate yield gains in our program. The difference in the findings may be explained by the differences in the genetic materials used for the present study; the cultivars evaluated in the present study were extra-early maturing, whereas Talabi et al (2017) evaluated early-maturing full-sib progenies. These include, among others, an increase in the size of the IITA maize breeding program to facilitate the use of higher selection intensity and an increase in the precision of selection to achieve higher heritability.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations